PENGARUH MACAM DAN DOSIS PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAMBILOTO (Andrographis paniculata Ness.) - Bambang Pujiasmanto; Pratignya Sunu; Toeranto Toeranto; Ali Imron (Faculty of Agriculture, Universitas Sebelas Maret, 2009)
Title : The Influence of Kind and Dose of Manure in Relation to Creat Growth and Yield (Andrographis paniculata Ness.)Creat were medicine plant which have great potential as raw materials of traditional medicine. Raw materials of Creat usually taken from native environment. The supply of creat’s raw materials which taken from original habitat give discontinued outcomes and cause its extinction. The appropriately agronomic production technique was expected to give better quality of medicinal plant’s raw materials. This research aimed to study kind and dose of manure for growth and outcomes of Creat. The research was conducted on October 2007 until January 2008 at Donoyudan Village, Kalijambe, Sragen. This research was arranged factorial in Completely Randomized Design (CRD). Which consist of two treatment factors and three replications. The first factor was the kind of manure, there were cow, goat and chicken manure. Second factor was dose of manure, consist of 25 g/plant, 50 g/plant and 75 g/plant. The research variables were the plant height, number of leaves, number of primary branch, fresh and dry weight of roots and shoots, and chlorophyll content. The research data were analyzed by F test in 5% level and continue by DMRT in 5% level, if the treatment were significant. The result of research showed that there was an interaction between kind and dose of manure, which were the number of primary branch, fresh weight of root, dry weight of shoot and root dry weight. Kind of manure showed that 75 g/plant of chicken able to increase the chlorophyll content, root fresh weight shoot dry weight and root dry weight. Keywords: Andrographis paniculata Nees., dose, manure